Review of Urinary Tract Infections in Pregnancy: Risks, Complications and Management - Patrycja Kałuziak; Jakub Parys; Agnieszka Mikosińska; Martyna Kaźmierczak; Marta Jajczak; Maciej Mossakowski; Aleksandra Witek; Mateusz Litwin; Stanisław Jesionek (Quality in Sport)
Background: Urinary tract infections (UTIs) are common in pregnant women due to significant changes during gestation. UTIs can affect any part of the urinary system and are typically caused by bacteria, though fungi and viruses can also be responsible. Asymptomatic bacteriuria (ASB is frequent in pregnancy and must be treated to prevent serious maternal and fetal complications. Routine screening for ASB is standard in prenatal care, and treatment with safe, effective antibiotics is essential. Preventive strategies also help reduce UTI during pregnancy.